2014
DOI: 10.1016/j.pmrj.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Association of Hip Cartilage Lesions and Cam‐Type Femoroacetabular Impingement With Movement Patterns: A Preliminary Study

Abstract: Objective Preliminary study to investigate the differences in hip movement patterns during different daily and athletic activities in individuals with cam-type femoroacetabular impingement (FAI) with and without cartilage lesions compared with controls. Design Controlled laboratory study using a Cross-sectional design. Setting Research Institution with Tertiary Care Medical Center. Participants Fifteen subjects [M:F – 13:2, Age- 31.6±9.7 years (22-52), BMI- 24.9±4.6 (18.8-38.4), FAI: Control = 7:8]. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 37 publications
6
72
1
Order By: Relevance
“…We did not find this difference in our data, but total ROM and maximum amplitude in the same plane are clearly not independent and the Page 12 of 23 A c c e p t e d M a n u s c r i p t 13 difference in outcome between studies may depend on features such as the definition of reference position. Sagittal plane ROM alterations in FAI were not reported in the two remaining studies [17,20] that specifically investigated participants with cam-type FAI.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…We did not find this difference in our data, but total ROM and maximum amplitude in the same plane are clearly not independent and the Page 12 of 23 A c c e p t e d M a n u s c r i p t 13 difference in outcome between studies may depend on features such as the definition of reference position. Sagittal plane ROM alterations in FAI were not reported in the two remaining studies [17,20] that specifically investigated participants with cam-type FAI.…”
Section: Resultsmentioning
confidence: 95%
“…We found no evidence for reduced ROM in the transverse plane during gait. Although two studies have reported reduced peak hip internal rotation in Page 13 of 23 A c c e p t e d M a n u s c r i p t 14 symptomatic FAI compared to controls with uncertain hip morphology [18,19], differences were not found in other studies [13,17,20]. It is widely accepted that measurement of transverse plane kinematics is less reliable (curve r² between 0.28 and 0.47 [26]) at the hip than the knee and ankle.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations